Evaluation of water quality due to human activities in the Sumber Awan spring and its chanel, Singosari Malang - Raden Ayu Shufairaa' Habiebah; Catur Retnaningdyah (University of Brawijaya, 2014)
The aims of this research was to determine the profile of water quality based on physico-chemical properties of water, water quality index, and to determine the influence of various human activities on water quality in the Sumber Awan Spring and its Channel, Singosari Malang. Water quality evaluation is done in the spring and six locations of the spring channel after passing through agricultural activities, public toilets and human settlements with the distance of each location approximately 200 m. Physico-chemical parameters of water were observed include turbidity, pH, DO, permanganate, TSS, nitrate, ammonium, and BOD. The monitoring data is used to perform the analysis of water quality profiles using ANOVA, cluster analysis based on Bray-Curtis similarity index and biplot as well as water quality indices include Prati's implicit Index of Pollution. The results showed that human activities that occur in the channel of Sumber Awan such as agriculture, human settlements and public toilets have been affected the water quality in this spring channel. It can be seen from the decreasing of water quality from upstream to downstream. Values of pH, ammonium, permanganate, TSS and nitrate fulfilled the quality standards for class I, DO for class II, BOD for class II-IV, based on Government Regulation No. 82/2001 and turbidity value based on WHO only station one fulfilled the quality standards. Based on Prati’s index calculations the water quality was categorized in acceptable (station 1-6) and slightly polluted (station 7). Keywords : Malang, physico-chemical water quality, Sumber Awan